The Level of Public Understanding of The Quick Response Indonesian Standard (QRIS) In Indonesia - Pristiyono, Pristiyono; Kanchanawongpaisan, Sipnarong; Ratnasari, Sri Langgeng (Social Sciences Insights Journal, 2023)
The increase in digital money transactions in 2021 indicates that the trend of digital transactions is increasingly widespread in Indonesia, besides that the trend of digital transactions is a way of changing people's shopping behavior, which previously went offline to online shopping through various marketplaces. The purpose of this study is to prove if the variables of performance expectancy, effort expectancy, social influence, and internet anxiety affect behavior intention. Then the author's sample set refers to the number of all 15 indicators x 7 = 105 samples. Then the sample in this study was set at 100 samples. Accidental sampling technique. The data collection technique uses primary data (in the form of a questionnaire) using Google Forms which is distributed offline and online and uses the necessary secondary data such as interviews, literature studies, and related agencies.  The results of the study prove that the hypothesis test between Performance Expectancy on Behavior Intention, it turns out that the hypothesis is rejected, the hypothesis test between Effort Expectancy on Behavior Intention, it turns out that the hypothesis is rejected, the hypothesis test between Social Influence on Behavior Intention, it turns out that the hypothesis is rejected and the hypothesis test between Anxiety Internet Behavior Intention, it turns out that the hypothesis is accepted